2016
DOI: 10.1016/j.biomaterials.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cell-laden polyelectrolyte hydrogels incorporating poly(l-Lysine) for applications in cartilage tissue engineering

Abstract: To address the lack of reliable long-term solutions for cartilage injuries, strategies in tissue engineering are beginning to leverage developmental processes to spur tissue regeneration. This study focuses on the use of poly(L-lysine) (PLL), previously shown to up-regulate mesenchymal condensation during developmental skeletogenesis in vitro, as an early chondrogenic stimulant of mesenchymal stem cells (MSCs). We characterized the effect of PLL incorporation on the swelling and degradation of oligo(poly(ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 75 publications
0
76
1
1
Order By: Relevance
“…(1,10,6467) Effective growth factor patterning requires an understanding of not only what growth factors are relevant to tissue formation and ingrowth and in what concentrations for each tissue, but also how factors interact to synergistically enhance or inhibit tissue formation. For example, it is well-understood that bone morphogenetic proteins (BMP-2, BMP-3, BMP-7) play a critical role in bone formation and remodeling.…”
Section: Target Tissues and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1,10,6467) Effective growth factor patterning requires an understanding of not only what growth factors are relevant to tissue formation and ingrowth and in what concentrations for each tissue, but also how factors interact to synergistically enhance or inhibit tissue formation. For example, it is well-understood that bone morphogenetic proteins (BMP-2, BMP-3, BMP-7) play a critical role in bone formation and remodeling.…”
Section: Target Tissues and Applicationsmentioning
confidence: 99%
“…A variety of previous reports using non-3DP hydrogels have demonstrated that bilayered composites with growth factor gradients can significantly improve cartilage and bone healing and tissue formation. (16,17,27,64,67,7277) These types of experiments, which created primarily bi- and triphasic constructs with discrete layers, can be considered precursors to the growth factor patterning techniques discussed here, and the incorporation of 3DP techniques to target these tissues is compelling when considering the ability to much more specifically design growth factor gradients. For example, Kundu et al used a multi-head extrusion-based printing system to pattern TGF-β within chondrocyte-encapsulated polycaprolactone/alginate.…”
Section: Target Tissues and Applicationsmentioning
confidence: 99%
“…Polimer yüksek basınç altında gaz ile doygun hale gelir ve daha sonra gazın çözeltiden uzaklaşması sağlanır. 23 …”
Section: Dondurarak Kurutmaunclassified
“…24,25,26 In this study, we have developed a biphasic CAN-PAC hydrogel with a seamless interface that simulated the properties of osteochondral tissue. The bilayer hydrogel was fabricated using a one-pot heat-initiated free radical polymerization method with a density difference between the upper layer and lower layer, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%